Cambridge Ielts intensive training speaking : (Tổng hợp, 2014)
As far as this book is concerned, it is arranged into 24 units with a total of five chapters whose themes centre upon the three parts of the IELTS Speaking test. Especially, questions which are typical in the IELTS Speaking test are provided so that you can be well prepeared for your actual test in the near future.